THE IMPORTANCE OF HALAL BI HALAL IN SOCIAL LIFE IN ACCORDANCE WITH CUSTOMS AND HABITS - Nur Yasin; Labibul Wildan (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTThe Qur'an contains explicit and implicit arguments. Explicit arguments are arguments that can be used as direct references, while implicit arguments are arguments that must be explained first by the experts because there are choices of conclusions in order to apply them. Basically, both explicit and implicit arguments must receive guidance from the experts of the Qur'an in order to maintain the majesty of the Qur'an.This work describes halal bi halal written using a socio-cultural approach, social reality theory, adat theory, urf and using views. This conclusion results that Halal Bihalal is a tradition that is not explicitly stated in the Qur'an but whose spirit has practiced the messages of the Qur'an.Keywords: Halal bi halal, social, adat and urf.